Determination of Cotton Fineness by an Air Flow Method - Abu Salma, Abbas Y. (Gezira Journal of Engineering and Applied Sciences, 2018)
Of all the physical properties of cotton, the fineness constitutes a property which arouses particular concern to spinners. Unlike, for example, fibre length, which is subject to a little effect of environmental conditions, the fineness of cotton is susceptible to many influences of environmental circu-mstances, e.g. temperature, relative humidity, maturity and particularly the amount of cotton irrigation water. Cotton, grown as a rain crop, can be more prone to immaturity than the cotton grown by artificial irrigation. Such immature cotton is weak and must be spun at a higher twist. This lowers the spinning production, since the production of this machine is inversely proportional to the amount of twist. This is a negative factor for production economy. This paper repre-sents a research work on fineness measurements of many cotton samples from a variety of countries, using the Micronaire as a testing appliance for fineness measurements. Factors affecting fineness are discussed and mathematical relationships of some important parameters are highlighted.